2021
DOI: 10.21203/rs.3.rs-1098214/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The burden and dynamics of hospital-acquired SARS-CoV-2 in England

Abstract: Hospital-based transmission played a dominant role in MERS-CoV and SARS-CoV epidemics but large-scale studies of its role in the SARS-CoV-2 pandemic are lacking. Such transmission risks spreading the virus to the most vulnerable individuals and can have wider-scale impacts through hospital-community interactions. Using data from acute hospitals in England we quantify within-hospital transmission, evaluate likely pathways of spread and factors associated with heightened transmission risk, and explore the wider … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…During the first wave in early 2020, they have been estimated to be the most important source of onward nosocomial transmission, both to patients and other HCWs [17,18]. However, other studies found that patient infection could result primarily from transmission from other patients [4,16,18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first wave in early 2020, they have been estimated to be the most important source of onward nosocomial transmission, both to patients and other HCWs [17,18]. However, other studies found that patient infection could result primarily from transmission from other patients [4,16,18].…”
Section: Resultsmentioning
confidence: 99%
“…Both patients and healthcare workers (HCWs) have been at high risk of SARS-CoV-2 infection throughout the pandemic, resulting in major nosocomial outbreaks worldwide [1,2]. In England, for instance, an estimated 20% of patients hospitalized with COVID-19 before August 2020 acquired their infection in hospital [3], while 95,000-167,000 patients became infected during their hospital stay between June 2020 and March 2021 [4]. Further, HCWs have experienced an estimated 1.6-to 3.4-fold higher risk of infection relative to the general population [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This same pattern has also been observed for SARS-CoV-2 where patients are most infectious shortly after they are initially infected, such that nosocomial cases account for much hospital-based transmission. 18,19 Focusing infection control efforts around these cases is an important priority. It should also be considered that genomically and epidemiologically linked pairs, could also represent 'co-secondary' cases, where both are acquired from a common, but unascertained source.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the key role played by healthcare settings during pandemic waves since 2020 worldwide [21] highlights the need for innovative strategies to control the nosocomial risk. Quarantine hospitals, which effectively isolated non-COVID patients from COVID patients and allowed to closely monitor at-risk HCWs, may provide interesting solutions to this challenge.…”
Section: Discussionmentioning
confidence: 99%